Sosialisasi Pembinaan Ekstrakurikuler Cabang Olahraga di SMAN 2 Lawe Sigala-Gala Kabupaten Aceh Tenggara - Afrizal, Afrizal; Br Nababan, Melfa; Hartono, Makmur; Nursafiah, Nursafiah; Suriani, Halisah; Khairuddin, Khairuddin (COVIT (Community Service of Tambusai), 2023)
One of the aims of extracurricular sports activities is to develop talents and interests towards achieving optimal sporting achievements. The aim of PPKM activities is to socialize the management and development of extracurricular sports activities in schools for teachers of physical education, sports and health at SMA Negeri 2 Lawe Sigala-gala. to provide information and knowledge to school principals, physical education teachers, sports and health, extracurricular sports coaches, students, parents and the educational academic community regarding procedures for managing and coaching extracurricular sports activities in an effort to achieve sports achievements at school. The final result that can be expected from this PKM activity is to provide additional knowledge to physical education, sports and health teachers regarding procedures for managing and coaching sports extracurricular activities so that they can be applied at school so that the goals of these sports extracurricular activities can be achieved effectively, efficiently, safely. , and smoothly. The method used in this activity is scientific discussion and questions and answers for 1 day, namely on Saturday 19 Agustus 2023 starting from 08.00-12.00 WIB.